2020
DOI: 10.1007/s00345-020-03170-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of vacuum-assisted closure (VAC) therapy in the management of FOURNIER’S gangrene: a retrospective multi-institutional cohort study

Abstract: Purpose To explore the role of vacuum assisted closure (VAC) therapy versus conventional dressings in the Fournier's gangrene wound therapy. Patients and Methods This is a retrospective multi-institutional cohort study. Data of 92 patients from nine centers between 2007 and 2018 were retrospectively analyzed. After surgery, patient having a local or a disseminated FG were managed with VAC therapy or with conventional dressings. The 10-weeks wound closure cumulative rate and OS were analyzed. Results Of the 92 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 24 publications
1
52
0
10
Order By: Relevance
“…The advantages of NPWT include persistent and complete drainage, effective infection control, reduced postoperative secondary necrosis, formation of new granulomatous tissue, and significant short-term improvement in wound status. [31][32][33] Some researchers have also suggested that NPWT reduces the incidence of septic shock, and organ failure. 31,34,35 Clinical diagnosis is particularly important in the treatment of NF, and a comprehensive diagnosis should be made in conjunction with the results of laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of NPWT include persistent and complete drainage, effective infection control, reduced postoperative secondary necrosis, formation of new granulomatous tissue, and significant short-term improvement in wound status. [31][32][33] Some researchers have also suggested that NPWT reduces the incidence of septic shock, and organ failure. 31,34,35 Clinical diagnosis is particularly important in the treatment of NF, and a comprehensive diagnosis should be made in conjunction with the results of laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Bei den retrospektiven Untersuchungen handelt es sich um 11 Fallserien mit insgesamt 860 FG Patienten [24][25][26][27][28][29][30][32][33][34][35] sowie eine retrospektive Kohortenanalyse mit epidemiologi-that there is urgent need for therapy improvement. New risk factors for higher mortality in FG have been identified in these studies, namely dyslipoproteinemia, diabetes mellitus, heart disease, as well as both acute and chronic kidney failure.…”
Section: Ergebnisse Aus Den Retrospektiven Studienmentioning
confidence: 99%
“…1 Überblick und Charakterisierung der eingeschlossenen Orignalarbeiten (n = 15). [25], Urologen oft nicht an der Therapie weiblicher FG Patienten beteiligt sind [26], Candida species oft in den Wunden der FG Patienten nachgewiesen werden, sodass eine primäre antimykotische Therapie evaluiert werden sollte [27] und dass die hyperbare Oxygenierung (HBO) als auch der vakuum-assistierte Wundverschluss (VAC) positive Effekte auf die Behandlungsergebnisse haben [28,32]. Die oben angesprochene Kohortenstudie konnte ebenfalls kein erhöhtes Risiko für FG bei der Einnahme von SGLT2-und DPP4-Hemmern (Antidiabetika) nachweisen [31].…”
Section: Ergebnisse Aus Den Retrospektiven Studienunclassified
“…Seguindo as diretrizes da European Association of Urology (EAU), sobre infecções urológicas, a abordagem inicial deve ser um desbridamento cirúrgico agressivo, completo e precoce (<24 h) do tecido necrótico, pois a cirurgia retardada e/ou inadequada pode resultar em maior mortalidade (Iacovelli et al, 2021). No entanto, mesmo após o manejo adequado para controlar a infecção, geralmente permanece uma grande ferida aberta; para cobrir isso, é necessária intervenção cirúrgica, como enxerto de pele, retalho local ou retalho livre.…”
Section: Introductionunclassified
“…Um atraso na cobertura desta ferida aberta residual pode resultar em infecção tardia, condição debilitante do paciente e até mesmo sepse generalizada (Lee, Jung, Kwon, & Jung, 2014). Deve ser administrado tratamento antibiótico parenteral empírico imediato; este pode então ser refinado, guiado por cultura microbiológica (Iacovelli et al, 2021).…”
Section: Introductionunclassified